2014
DOI: 10.7895/ijadr.v3i3.154
|View full text |Cite
|
Sign up to set email alerts
|

Availability restrictions and alcohol consumption: A case of restricted hours of alcohol sales in Russian regions

Abstract: Kolosnitsyna, M., Sitdikov, M., & Khorkina, N. (2014). Availability restrictions and alcohol consumption: A case of restricted hours of alcohol sales in Russian regions. The International Journal Of Alcohol And Drug Research, 3(3), 193 – 201. doi:http://dx.doi.org/10.7895/ijadr.v3i3.154Aim: To determine how new restrictions on hours of alcohol retail sales influence alcohol consumption in Russia.Design: Natural experiment with combined regional and micro-data.Setting/Participants: Cross-sectional samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 19 publications
(11 reference statements)
0
28
0
1
Order By: Relevance
“…Kolosnitsyna, Sitdikov, & Khorkina (2014) used cross-sectional samples from the Russian Longitudinal Monitoring Survey to examine the impacts of a natural experiment involving variations in hours of sale. They concluded that restrictions in hours of sale, especially evening hours, were linked with lower consumption levels.…”
Section: Availability -Control System Outlet Density Days and Hoursmentioning
confidence: 99%
“…Kolosnitsyna, Sitdikov, & Khorkina (2014) used cross-sectional samples from the Russian Longitudinal Monitoring Survey to examine the impacts of a natural experiment involving variations in hours of sale. They concluded that restrictions in hours of sale, especially evening hours, were linked with lower consumption levels.…”
Section: Availability -Control System Outlet Density Days and Hoursmentioning
confidence: 99%
“…More recent research from Norway suggests that a one hour increase in trading hours on weekend nights affects a 20% increase in violent crime in city centres (20). Other recent studies from Russia, Brazil, the Netherlands and the USA concur that there is a link between extended trading hours, increased alcohol consumption (21), injuries (22) and violent crime (23,24).…”
Section: Introductionmentioning
confidence: 97%
“…In letteratura alcune fonti riportano l'efficacia protettiva delle politiche restrittive sul consumo di bevande alcoliche (aumento di tasse e prezzi e abbassamento dell'età minima per l'acquisto di bevande alcoliche) nei confronti dei tassi di suicidio (Pridemore et al, 2009(Pridemore et al, , 2013Xuan et al, 2016). Limitazioni alla disponibilità di, e accessibilità a, luoghi e orari di vendita sono state dimostrate associarsi a minori consumi alcolici e a minori danni alcol-correlati (Gruenewald, 2011;Wicki e Gmel, 2011;Kypri et al, 2011;Cook et al, 2014;Kolosnitsyna et al, 2014), mentre l'estensione degli orari e l'aumento di densità dei punti vendita aumentano i danni associati al bere (Stockwell & Chikritzhs 2009;Hahn et al, 2010;Lippy et al, 2014;Xuan et al, 2015). In modo opposto, tuttavia, Green, Heywood e Navarro (2014) hanno rilevato un'associazione tra l'estensione degli orari di chiusura dei bar in Inghilterra e in Galles e una diminuzione degli incidenti stradali, specie tra gli automobilisti giovani.…”
Section: Le Misure DI Politica Alcologica E Il Loro Impatto Sul Consuunclassified